НАПРЯМКИ УДОСКОНАЛЕННЯ ВЗАЄМОДІЇ СУБ’ЄКТІВ ЗАБЕЗПЕЧЕННЯ КІБЕРБЕЗПЕКИ УКРАЇНИ - Бухарев, Владислав Вікторович (SUPREMANCE OF LAW, 2018)
In the article, based on the analysis of scientific views of scientists and the norms of the current legislation of Ukraine, possible ways of improving the interaction of subjects of the cyber security of Ukraine are identified. It is noted that under the interaction of the subjects of providing cybersecurity it is necessary to understand their joint co-ordinated activity, which is aimed at achieving the only goal - to ensure the proper state of cybersecurity in Ukraine. Characteristic features of such interaction include: 1) the sole purpose of joint activity; 2) the presence of several or more subjects; 3) the legal basis for the activity is obligatory; 4) clearly defined administrative and legal status of each subject; 5) consistency of measures regarding the purpose, place, time, methods. Proposed to specific forms of interaction of actors in the provision of cyber security in Ukraine include: 1) conducting joint interagency meetings; 2) the exchange of operational information on the state of security of cybersecurity, as well as on measures that have already been implemented by each subject of interaction; 3) the development of joint programs to combat cybercrime and outline the main areas of joint activity; 4) joint participation in conducting separate investigatory and investigative actions; 5) formation of joint consultative and advisory and expert bodies, councils, commissions. It is proved that the methods of interaction are a set of methods and techniques aimed at establishing effective interaction between actors authorized to provide cybersecurity in Ukraine. Such methods of interaction include: 1) a staffing method that involves the active training of representatives of certain bodies of the specifics of the work of others, which in turn promotes the establishment of effective interaction between departments; 2) the method of mutual information provision, which is to provide the actors of cooperation to each other all the necessary information for more open and efficient interaction; 3) the method of control, that is, the parties (subjects) of interaction are able to perform mutual control of each other during the joint activity; 4) planning and forecasting methods; 5) economic method, which provides for the creation of the appropriate material base for joint activities and others.